UV light and adaptive divergence of leaf physiology, anatomy, and ultrastructure drive heat stress tolerance in genetically distant grapevines - Fernandes de Oliveira, Ana; Piga, Giovanni Kamal; Najoui, Soumiya; Becca, Giovanna; Marceddu, Salvatore; Rigoldi, Maria Pia; Satta, Daniela; Bagella, Simonetta; Nieddu, Giovanni (Frontiers in Plant Science, 2024)
Genetic basis of plant response to light and heat stresses have been unveiled and different molecular mechanisms of leaf cell homeostasis to keep high physiological performances were recognized in grapevine varieties. However, the ability to develop heat stress tolerance strategies must be further elucidated, since the morpho-anatomical and physiological traits involved may vary with genotype × environment combination, stress intensity and duration. A three-year experiment was conducted on potted plants of Sardinian red grapevines cultivar Cannonau (syn. Grenache) and Carignano (syn. Carignan), exposed to prolonged heat stress inside a UV-blocking greenhouse, either submitted to low daily UV-B doses of 4.63 kJ m‒2 d‒1 (+UV) or to 0 kJ m‒2 d‒1 (‒UV), and compared to a control (C) exposed to solar radiation (4.05 kJ m‒2 d‒1 average UV-B dose). Irrigation was supplied to avoid water stress and canopy light and thermal microclimate were monitored continuously. Heat stress exceeded 1/3 of duration inside the greenhouse and 6% in C. In vivo spectroscopy, including leaf reflectance and fluorescence allowed for characterizing different pattern of leaf traits and metabolites involved in oxidative stress protection. Cannonau showed lower stomatal conductance under C (200 mmol m‒2 s‒1) but more than twice the values inside the greenhouse (400 to 900 mmol m‒2 s‒1), where water use efficiency was reduced similarly in both varieties. Under severe heat stress and ‒UV Cannonau showed sharper decrease in primary photochemical, higher leaf pigment reflectance indexes and leaf mass area. UV-B increased leaf pigments, especially in Carignano and different leaf cell regulatory traits to prevent oxidative damage were observed in leaf cross-sections. Heat stress induced chloroplast swelling, plastoglobules diffusion and accumulation of secretion deposits in both varieties, aggravated in Cannonau ‒UV by cell vacuolation, membrane dilation and diffused leaf blade spot swelling. Conversely, in Carignano UV-B, cell wall barriers and calcium oxalate crystals proliferated in mesophyll cells. These responses suggest an adaptive divergence among cultivars to prolonged heat stress and UV-B light. Further research on grapevine biodiversity, heat and UV-B light interactions may give new insights on the extent of stress tolerance, to improve viticulture adaptive strategies in climate change hotspots.